2015
DOI: 10.1155/2015/739325
|View full text |Cite
|
Sign up to set email alerts
|

Distribution Pattern of Metals in Atmospheric Settling Dust along Roads in Kano Metropolis, Nigeria

Abstract: The sequential extraction of Cd, Cr, Ni, Pb, Cu, and Zn in atmospheric dust particles collected along ten high traffic roads in Kano metropolis was carried out. Analyses of metals in the extracts were done using flame atomic absorption spectrometry (FAAS). The samples analyzed for metals indicated high levels of Cd, Cr, Ni, Pb, Cu, and Zn in the atmospheric dust samples. The sequential extractions that showed significant amount of Cd were associated with CO 3 2− and Fe-MnO fractions especially during the dry s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
8
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 27 publications
1
8
0
Order By: Relevance
“…The major sources of these metals include electronic wastes, traffic emission, or wearing of tire. The significance of high amounts of Zn in this fraction agrees with earlier observation of Okunola et al [ 8 ] that the metal is considered to be occluded inside crystalline structure and not readily available for absorption. This observation is also consistent with earlier reports in urban street dust in Nigeria.…”
Section: Resultssupporting
confidence: 90%
See 1 more Smart Citation
“…The major sources of these metals include electronic wastes, traffic emission, or wearing of tire. The significance of high amounts of Zn in this fraction agrees with earlier observation of Okunola et al [ 8 ] that the metal is considered to be occluded inside crystalline structure and not readily available for absorption. This observation is also consistent with earlier reports in urban street dust in Nigeria.…”
Section: Resultssupporting
confidence: 90%
“…In most of these studies, elevated levels of heavy metals have been observed in atmospheric suspended dust in most cities. Okunola et al [ 8 ] reported the presence of heavy metals such as Cd, Cr, Ni, Pb, Cu, and Zn in atmospheric settling dust in Kano metropolis of Nigeria. Meanwhile, Mafuyai et al [ 9 ] reported that the concentrations of some heavy metals were found to be far above the standard limits prescribed by WHO for respirable dust in Jos, Nigeria.…”
Section: Introductionmentioning
confidence: 99%
“…Quite a lot of researchers have investigated elemental compositions of suspended particulate matters in cities worldwide [4][5][6][7][8][9]. In most of these studies, elevated levels of trace elements have been observed in atmospheric suspended dust in most cities.…”
Section: Introductionmentioning
confidence: 99%
“…For example, Okunola et al [8] reported the presence of Cd, Cr, Ni, Pb, Cu, and Zn in atmospheric settling dust in Kano metropolis of Nigeria. Meanwhile, Mafuyai et al [9] reported that the concentrations of some trace elements were found to be far above the standard limits prescribed by WHO for respirable dust in Jos, Nigeria. Therefore, urban dwellers are exposed to considerable amounts of these elements through inhalation of airborne particulates.…”
Section: Introductionmentioning
confidence: 99%
“…Numerous researchers have investigated elemental compositions of suspended particulate matters in cities worldwide; Monterry, Mexico [4], Tehran, Iran [5], Nigerian cities [6][7][8][9][10]. In most of these studies, it was observed that urban dusts were typically elevated by total metal concentrations above the standard limits prescribed by WHO for respirable dust in most cities.…”
Section: Introductionmentioning
confidence: 99%